Understanding inflation dynamics: The role of government expenditures - Chang Liu; Yinxi Xie (Bank of Canada, 2023)
This paper studies the impact government expenditure has on inflation by examining an augmented Phillips curve implied from a structural New Keynesian model, Our estimation results, based on external instruments, show that the augmented Phillips curve has a flatter slope than the canonical specification and that government expenditure has a negative coefficient, Changes in government expenditure account for a substantial portion of inflation variations and provide new insights into the "missing disinflation" puzzle, We also find that inflation and inflation expectations respond negatively to fiscal spending shocks, reaffirming the supply-side channel through which inflation responds to fiscal expansions.
Keywords: E3; E62; E63; 330; Inflation and prices; Fiscal policy; Central bank research